Strategi Pengembangan Perilaku Komunikasi Guru Responsif Gender - Ernita Arif; Aida Vitayala S Hubeis; Basita Ginting Sugihen; Ninuk Purnaningsih; Amiruddin Saleh (Jurnal Penyuluhan, 2014)
The teacher is a strategic factor in the learning process. For that teachers must have good skills, especially the ability to communicate, because the whole learning process is closely related to communication. But the reality has not been able to optimize the ability of the teacher to the students of boys and girls. This study aims to develop the communication behavior of a gender responsive teachers. The study was designed as ekplanatory survey research conducted by two hundred the number of respondents using Taro Yamane formula. This research was conducted in the city of Padang and Padang Pariaman since June-December 2013. Results showed that the strategy of development of gender responsive teacher communication behaviors through strengthening the internal and external factors.Keywords: teacher, strategies, gender responsive, learning process